Bone cysts in children and adolescents (literature review) - Verdiyev, Farhad (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The author carried out an analytical review of scientific information on the issue of the treatment of bone cysts in children and adolescents. He presented the classification, etiology and pathogenesis of the disease. The methods of diagnosis, treatment and assessment of its outcomes were analyzed. It was noted that there is no consensus on treatment strategy of bone cysts among experts. Despite on numerous methods of surgical treatment of this disease the percentage of relapse remains high. The author considers the combined use of surgical techniques, distraction osteosynthesis and puncture drug therapy as a promising trend.